Post-Triassic mineralization in central New Brunswick: implications of the McBean Brook Zn-Pb-Ag occurrence - Crosby, Russell; Greenough, John; Hattie, Donald; Venugopal, Dodda (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1990)
Mineralization at the McBean Brook Zn-Pb-Ag prospect (central New Brunswick) occurs in fault-brecciated Ordovician metasedimentary rocks and Mesozoic diabase dyke rocks. The dyke is interpreted to form part of the early Jurassic Caraquet dyke because it is on strike with the Caraquet dyke, has the same NE-SW orientation, and is similar in mineralogy (containing large plagioclase phenocrysts and olivine) and chemistry (e.g., Ti02 and Ga concentrations and Zr/Y ratios). Thus the mineralization at McBean Brook, consisting of carbonate, quartz, pyrite, pyrrhotite, sphalerite, galena, and chalcopyrite, is probably early Jurassic or younger. Available data indicate chemical similarity with Ordovician massive sulphide deposits near Bathurst, New Brunswick, possibly reflecting the control of similar source rocks on the composition of hydrothermal solutions despite different tectonic conditions. Many Mesozoic or younger hydrothermal sulphide, magnetite and native copper showings occur in the Appalachian belt. Although these tend to be Pb-, Fe- or Cu-dominated, many have the reactivated fault zone-diabase association like that at McBean Brook. A widespread rift-related early Mesozoic episode of low-temperature hydrothermal activity may have affected the Appalachians, a possibility that should be kept in mind when estimating ages for ore deposits.